A case report of Leri-Weill dyschondrosteosis with bilateral Madelung deformity managed by Vicker’s ligament release and dome osteotomy - Rajan Sujatha, Adarsh; Harafan, Abdulla; Gopi, Jipin; K. M., Sanjai; Krishna, Anju; Roshan, Shisham Hashim (International Journal of Research in Orthopaedics, 2025)
Leri-Weill dyschondrosteosis (LWD) is an uncommon skeletal dysplasia marked by mesomelic limb shortening and the typical wrist abnormality known as Madelung deformity. It results from reduced activity of the SHOX gene. We report a 9-year-old girl with a 4-year history of progressive, painless deformities affecting both forearms. Examination revealed short stature (116 cm), bilateral forearm shortening, dorsal prominence of the ulna, and restricted ulnar deviation and elbow extension. Genetic evaluation confirmed a pathogenic SHOX mutation. Surgical treatment with bilateral distal radius dome osteotomy combined with Vicker’s ligament release was performed. Postoperatively, the patient achieved good cosmetic correction and marked functional improvement. This case emphasizes the importance of evaluating SHOX-related disorders in children presenting with short stature and wrist deformity. Combined ligament release with corrective osteotomy offers both functional and cosmetic benefit in LWD patients.